2004
DOI: 10.1002/bjs.4801
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial comparing radioisotope occult lesion localization and wire-guided excision for biopsy of occult breast lesions

Abstract: ROLL and wire-guided localization were similarly effective for breast biopsy, but ROLL was easier for both radiologist and surgeon, and less painful for the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
73
3
16

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(99 citation statements)
references
References 5 publications
7
73
3
16
Order By: Relevance
“…PEML'nın sayısının artması, bu lezyonların işaretlenmesinde güvenli, etkili, ideal bir yöntem arayışını gerekli kılmıştır (25). İdeal yöntem lezyonun tamamen çıkarıl-masını sağlayan ve gereksiz sağlam meme dokusu eksizyonunu en aza indiren bir yöntem olmalıdır (9,10,(28)(29)(30). PEML'nın lokalizasyonu için birkaç yöntem tanımlanmıştır.…”
Section: Tartışma Ve Sonuçlarunclassified
See 2 more Smart Citations
“…PEML'nın sayısının artması, bu lezyonların işaretlenmesinde güvenli, etkili, ideal bir yöntem arayışını gerekli kılmıştır (25). İdeal yöntem lezyonun tamamen çıkarıl-masını sağlayan ve gereksiz sağlam meme dokusu eksizyonunu en aza indiren bir yöntem olmalıdır (9,10,(28)(29)(30). PEML'nın lokalizasyonu için birkaç yöntem tanımlanmıştır.…”
Section: Tartışma Ve Sonuçlarunclassified
“…Yapılan çalışmaların çoğunda radyonüklid madde ile işaretlemenin güvenilir ve etkili olduğu kanıtlanmıştır (17,26,28,29,(35)(36)(37)(38)(39). Radyonüklid madde ile işaretlemede başarı oranları literatürde %92 ile %100 arasında değişmektedir (17,25,36,39,40).…”
Section: Tartışma Ve Sonuçlarunclassified
See 1 more Smart Citation
“…Most importantly, the resemblance of RSL and ROLL to the performance of SLNB which is a standard practice means that breast surgeons who have never performed either technique formally will still be familiar with the principles and possess the necessary skills to learn both techniques rapidly. Certainly studies comparing RSL and ROLL to WGL have suggested that surgeons favoured the radio-guided techniques over WGL in terms of ease of performance [17,46].…”
mentioning
confidence: 99%
“…It can be demonstrated from what has been presented from the published evidence that it is not possible to identify any differences in clinical outcomes including complications between ROLL and RSL to suggest the superiority of one over the other. Both techniques have proven to be competitively priced in comparison with WGL [7,10,11] and to have no significant learning curves for surgeons [7,8,17,46]. The single area where a difference can be identified currently is in terms of the flexibility and timing of RSL over ROLL.…”
mentioning
confidence: 99%